(untitled) (Nexo Revista Científica, 2021)
This article discusses an approach to monitoring optimization in telecommunication networks with packet routing. Mathematical model of data networking with accounting for monitoring traffic structure is described, optimization task is determined. Main attention is paid to model development on the basis of queueing theory in order to generation of reserve capacity in system. The main concept is that comparatively simple structure of monitoring network is imposed on physical structure of telecommunication network. The modeling is aimed at selection of optimum parameters of monitoring system, solution techniques for similar task are proposed. The obtained optimization task is sufficiently complicated, subsequent attempts should be aimed at searching for conditions which would enable introduction of some constraints in order to simplify its solution without noticeable loss of the model adequacy. This is especially important for asynchronous task of monitoring, it should be based on selection of the most acceptable type of objective function (linear or quadratic). Management system structure of terminal equipment monitoring has been developed for railway sector on the basis of SNMP V3. The system would permit to improve confidence level of data received from measuring system about electrical parameters of route cables, thus decreasing human errors upon classification of emergency situations occurring in communication networks.